2018
DOI: 10.3390/su10082935
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Hazardous Chemical Accidents in China between 2006 and 2017

Abstract: Abstract:From the perspective of characteristics and causes, probability and forecast, and safety management evaluation, this paper analyzes 3974 hazardous chemical casualty accidents that occurred between 2006 and 2017 in China. The trends, monthly and hourly distributions, lifecycles, chemical and accident types, and the direct and indirect causes of casualty accidents are analyzed first. To estimate the probability of casualty accidents, the Poisson regression model is employed. The time series model is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Because of the large quantity, variety and high risk of hazardous chemicals, the potential storage hazards can exceed those of the production, transportation and use of hazardous chemicals. Human factors play an important role in the occurrence of hazardous chemical accidents in China [ 1 , 2 ]. Therefore, it is necessary to analyze and identify human factors in hazardous chemical storage accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the large quantity, variety and high risk of hazardous chemicals, the potential storage hazards can exceed those of the production, transportation and use of hazardous chemicals. Human factors play an important role in the occurrence of hazardous chemical accidents in China [ 1 , 2 ]. Therefore, it is necessary to analyze and identify human factors in hazardous chemical storage accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we define ϕ D , ϕ P , and ϕ A in Equations (6), (7), and (8) as the percentage difference between a solution and the optimum reached when minimizing an objective in isolation (denoted *):…”
Section: Methodsmentioning
confidence: 99%
“…The safe disposal of these materials is crucial for ensuring that humans do not encounter potentially dangerous and life-threatening chemicals. While highway infrastructure may ultimately allow for the fastest viable transportation of these materials to their eventual disposal sites, it also poses significant risks to human safety in the event of a traffic accident or unintended leakage [7]. In many cases, local, state, and federal laws dictate that highway routing schemes for transportation of hazardous materials must be designed to preserve human safety.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of hazardous chemical accidents (HCAs) in China has shown a downward trend in recent years [1], there are still a large number of casualties and economic losses caused by HCAs. Based on the analysis of 3974 HCAs in China from 2006 to 2018, it has been found that 50.57% of HCAs were caused by unsafe behavior [2]. Similarly, it has been found that 35% of all HCAs in China from 2007 to 2010 were caused by the violation of operation rules [3], and 44% of all HCAs in China from 2011 to 2013 were caused by unsafe behavior [4].…”
Section: Introductionmentioning
confidence: 99%